Aeromonas sobria Induces Proinflammatory Cytokines Production in Mouse Macrophages via Activating NLRP3 Inflammasome Signaling Pathways - Zhang, Wei; Li, Zhixing; Yang, Haitao; Wang, Guanglu; Liu, Gang; Wang, Yu; Bello, Babatunde Kazeem; Zhao, Panpan; Liang, Wei; Dong, Jingquan (Frontiers in Cellular and Infection Microbiology, 2021)
Aeromonas sobria, a common conditional pathogenic bacteria, is widely distributed in the environment and causes gastroenteritis in humans or septicemia in fish. Of all Aeromonas species, A. sobria is the most frequently isolated from human infections especially in immunocompromised subjects. Innate immunity is the first protection system of organism to resist non-specific pathogens invasion; however, the immune response process of hosts against A. sobria infection reunexplored. The present study established an A. sobria infection model using primary mouse peritoneal macrophages (PMφs). The adherence and cytotoxicity of A. sobria on PMφs were determined by May-Grünwald Giemsa staining and LDH release measurement. Pro-inflammatory cytokine expression levels were measured using qPCR, western blotting, and ELISA methods. We also investigated the levels of ASC oligomerization and determined the roles of active caspase-1 in IL-1β secretion through inhibition assays and explored the activated pattern recognition receptors through immunofluorescence. We further elucidated the roles of activated inflammasome in regulating the host’s inflammatory response through inhibition combined with ELISA assays. Our results showed that A. sobria induced lytic cell death and LDH release, whereas it had no adhesive properties on PMφs. A. sobria triggered various proinflammatory cytokine transcription level upregulation, and IL-1β occupied the highest levels. The pro-IL-1β protein expression levels increased in a dose-dependent manner with MOI ranging from 1 to 100. This process was regulated by ASC-dependent inflammasome, which cleavage pro-IL-1β into active IL-1β p17 with activated caspase-1 p20. Meanwhile, the expression levels of NLRP3 receptor significantly increased, location analysis revealed puncta-like surrounding nuclear, and inhibition of NLRP3 inflammasome downregulated caspase-1 activation and IL-1β secretion. Blocking of NLRP3 inflammasome activation through K+ efflux and cathepsin B or caspase approaches downregulated A. sobria–induced proinflammatory cytokine production. Overall, these data indicated that A. sobria induced proinflammatory cytokine production in PMφs through activating NLRP3 inflammasome signaling pathways.